A new record for the flora of Turkey: Lepidium didymum L. (Brassicaceae) - (:unkn) unknown (My University, 2013)
Lepidium didymum L. (Brassicaceae) türü Türkiye florası için (A8 Artvin) ilk defa kaydedilmiştir. Yeni kaydın detaylı morfolojik betimi ve fotoğrafı verilmiştir.

Lepidium didymum L. (Brassicaceae) is recorded for the first time (A8 Artvin) for the flora of Turkey. Detailed morphological description, includingphotograph of the new record is given.
Türkiye florasıiçin yeni bir kayıt: Lepidium didymum L. (Brassicaceae)
Keywords: Biyoloji